Comparative Analysis of the Influence of Transport Modes on Tourism: High-Speed Rail or Air? City-Level Evidence from China. Issue 2 (February 2023) - Chen, Jieping; Yan, Na; Lin, Shanlang; Chen, Shijun
This paper quantifies and compares the influence of two modes of transport on tourism, namely, high-speed rail (HSR) and air travel, and explores their substitute or complementary relationships. To facilitate the analysis, we apply data from 291 prefectural administrative cities in China from 2003 to 2019. Empirical tests show that both modes have a significant positive influence on the development of tourism. Moreover, the effect of air travel is greater than that of HSR. The findings remain robust and reliable with changes in the explanatory variables and sample size, and with regard to time window adjustment and endogeneity. Further, we explore the differences in the strength of the influences and find the two modes exhibit various effects according to regional heterogeneity. Finally, we investigate the joint effect of the two modes and find the existence of a substitute relationship. However, the relationship changes to complementary in specific areas. The findings of this paper provide important implications for the development of the regional tourism economy and the spatial layout of the transport infrastructure.